Identification of a crime perpretator based on trace evidence - Dariusz Szydłowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2018)
The application of advanced methods of trace identification at a crime scene has made a substantial contribution to the identification of offenders. An accurate identification as well as preservation of forensic traces at a crime scene are key determinants of the methods’ usage. The application of appropriate forensic traces identification and preservation techniques has been presented in the paper, including selected case studies.